Life sciences and technologies for developing countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Since 1983 the European Community has coordinated its research and technical development (RTD) activities through annual Framework Programmes. So far, there have been two Framework Programmes. On 23 April 1990, the Council adopted the Third...